(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
In today’s world web applications are integral part of our day today life. Currently there are infinite numbers of web users around the world. These web applications allows users to use the services provided by them upon justa simple clicks from anywhere in the world. Due to rapid growth as well as competition in the business the service providers are making use of the web applications to attract the user. Some of the common examples of the web applications are banking applications, social networking applications, ecommerce applications etc. There exists a variety of attacks that imposes threat on these web applications. One of such attack is known as SQL Injection attack. Research has shown that about 64% of the overall web applications running worldwide are prone to SQLIA. SQL injection is a SQL code injection technique, which forces the database to execute malicious SQL commands that can perform unwanted actions on the underlying database such as getting access to private information or even deleting the entire tables or the database itself. So the prevention against such an attack is must for the web applications. Various research work in this area have been carried out so as to provide better and more accurate defence mechanism against SQLIA, but still the incident of SQLIA are reported time and again even with big cloud service providers. This paper reviews some latest work from some of the best journals in this area.